2022
DOI: 10.1002/jor.25392
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome and CEUS‐assessed deltoid muscle vitality after fracture‐specific versus standard prosthetic design in reverse shoulder arthroplasty for trauma

Abstract: Functional outcome after reverse-shoulder-arthroplasty (RSA) in proximal humerus fractures (PHF) depends on deltoid muscle integrity and successful reattachment of the tuberosities for best possible recovery of rotator-cuff function. In this monocentric, prospective, randomized, controlled trial we investigated whether a reverse-fracture-prosthesis (RFP) with a metaphyseal fenestrated stem achieved superior shoulder and muscle function compared to a common reverse-prosthesis (RP) design for patients with PHF. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Eleven RCTs (57.9%) were Appropriately Statistically Powered (ASP) meaning they recruited a sufficient sample size to satisfy a requirement of at least 80% power, 9 , 10 , 16 , 19 , 20 , 24 , 33 , 35 , 40 , 43 , 48 while 8 RCTs (42%) were statistically underpowered (SUP) as they did not recruit a population sufficient to achieve 80% power. 7 , 15 , 18 , 23 , 41 , 42 , 44 , 45 The ASP subgroup had a greater median trial FI than the SUP group at 5 (4.50-5) vs. 4 (3.75-4.13). We observed an association between higher powered studies and those with higher FIs, with data shown fully in Table II .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Eleven RCTs (57.9%) were Appropriately Statistically Powered (ASP) meaning they recruited a sufficient sample size to satisfy a requirement of at least 80% power, 9 , 10 , 16 , 19 , 20 , 24 , 33 , 35 , 40 , 43 , 48 while 8 RCTs (42%) were statistically underpowered (SUP) as they did not recruit a population sufficient to achieve 80% power. 7 , 15 , 18 , 23 , 41 , 42 , 44 , 45 The ASP subgroup had a greater median trial FI than the SUP group at 5 (4.50-5) vs. 4 (3.75-4.13). We observed an association between higher powered studies and those with higher FIs, with data shown fully in Table II .…”
Section: Resultsmentioning
confidence: 95%
“…The quality of evidence was assessed using the ROB-II tool. 38 No RCTs were found to be at a high ROB, 13 were found to have a low ROB, 9 , 10 , 15 , 19 , 20 , 23 , 24 , 33 , 40 , 43 , 44 , 45 , 48 while for 6 there were some concerns about potential bias 7 , 16 , 18 , 35 , 41 , 42 ( Supplementary Appendix S1 ). The current impact factor of the journals in which the included RCTs are published had a mean of 3.6 ± 0.6, with 14 (74%) of the RCTs published in the Journal of Shoulder and Elbow Surgery, 2 in the Journal of Bone and Joint, and 1 each in Journal of Orthopaedic Research, Journal of Orthopaedic Trauma, and Archives of Orthopaedic and Trauma Surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Although there is some evidence that fracture stem is associated with higher tuberosity healing in HA, there is insufficient evidence in literature supporting superiority of a fracture stem over standard stem in RTSA [ 67 , 68 ]. Multiple retrospective studies and systematic reviews report conflicting evidence with respect to tuberosity healing and or shoulder function when using a fracture stem compared to a standard humeral stem RTSA for PHFs [ 66 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ].…”
Section: Special Considerations For Rtsa For Fracturesmentioning
confidence: 99%